Issues in Continuous 24-h Core Body Temperature Monitoring in Humans Using an Ingestible Capsule Telemetric Sensor - Monnard, Cathriona R.; Fares, Elie-Jacques; Calonne, Julie; Miles-Chan, Jennifer L.; Montani, Jean-Pierre; Durrer, Dominique; Schutz, Yves; Dulloo, Abdul G. (Frontiers in Endocrinology, 2017)
Background There is increasing interest in the use of pill-sized ingestible capsule telemetric sensors for assessing core body temperature (Tc) as a potential indicator of variability in metabolic efficiency and thrifty metabolic traits. The aim of this study was to investigate the feasibility and accuracy of measuring Tc using the CorTemp® system. Methods Tc was measured over an average of 20 h in 27 human subjects, with measurements of energy expenditure made in the overnight fasted state at rest, during standardized low-intensity physical activity and after a 600 kcal mixed meal. Validation of accuracy of the capsule sensors was made ex vivo against mercury and electronic thermometers across the physiological range (35–40°C) in morning and afternoon of 2 or 3 consecutive days. Comparisons between capsule sensors and thermometers were made using Bland–Altman analysis. Systematic bias, error, and temperature drift over time were assessed. Results The circadian Tc profile classically reported in free-living humans was confirmed. Significant increases in Tc (+0.2°C) were found in response to low-power cycling at 40–50 W (~3–4 METs), but no changes in Tc were detectable during low-level isometric leg press exercise (<2 METs) or during the peak postprandial thermogenesis induced by the 600 kcal meal. Issues of particular interest include fast “turbo” gut transit with expulsion time of <15 h after capsule ingestion in one out of every five subjects and sudden erratic readings in teletransmission of Tc. Furthermore, ex vivo validation revealed a substantial mean bias (exceeding ±0.5°C) between the Tc capsule readings and mercury or electronic thermometers in half of the capsules. When examined over 2 or 3 days, the initial bias (small or large) drifted in excess of ±0.5°C in one out of every four capsules. Conclusion Since Tc is regulated within a very narrow range in the healthy homeotherm’s body (within 1°C), physiological investigations of Tc require great accuracy and precision (better than 0.1°C). Although ingestible capsule methodology appears of great interest for non-invasively monitoring the transit gut temperature, new technology requires a reduction in the inherent error of measurement and elimination of temperature drift and warrants more interlaboratory investigation on the above factors.